Christianity in the Foreign Policy of the Sassanid and Ilkhanid Dynasties - Murat Tural (Tarih Dergisi)
This study comparatively deals with Christianity as a factor in the foreign policy of the Sassanid Dynasty as the last pre-Islamic Persian dynasty of the geography of Iran, and the Ilkhanid Dynasty that converted to Islam toward the end of its rule. The two elements that dominated Iran and its surroundings, one by revolution and the other by occupation, are seen to have been forced to pursue a Christian-centered foreign policy soon after their establishment. In this article does cross-examine the intersecting and diverging aspects of the Roman-Persian and Ilkhanid-European relationship. This study; analyzes the traces of continuity and change in Iran at the time of these two political entities mainly through issues such as the religious beliefs of the Sassanid and Ilkhanid rulers, the Christian wives of the shahenshahs and ilkhans, the Catholicos, the leader of the Eastern Church, and the Christian persecution.